Weak Dust Activity Near a Geologically Young Surface Revealed by Chang'E‐3 Mission. Issue 16 (16th August 2019) - Yan, Qi; Zhang, Xiaoping; Xie, Lianghai; Guo, Dawei; Li, Yong; Xu, Yi; Xiao, Zhiyong; Di, Kaichang; Xiao, Long
Abstract: In spite of great scientific and engineering interests in lunar exploration, natural dust activity near the Moon surface remains unclear. According to distinct reflectance features of lunar rocks and regolith observed by Chang'E‐3 mission, long‐term dust activity near a young surface is quantified with a new method. We found that a dust deposition upper line on rocks is about 28 cm above the ground. Below this line, the quantity of dust deposits becomes smaller as the altitude ascends, whereas above the line, no visible or only negligible amount of dust is distributed on the rocks. This dust distribution pattern could be explained by dust electrostatic levitation process. The results indicate distinctively weak long‐term dust activity near the young surface and suggest possible selection of geologically young regions as landing sites or lunar bases to minimize the effect of dust grains. Key Points: Chang'E‐3 observations show long‐term deposition upper line on rocks about 28 cm above the ground nearby This hight indicates the probable electrostatic levitation altitudes of most lofted grains in this area The results imply distinctively weak long‐term dust activity near the young surface at this site